Geometric Estimates of the First Eigenvalue of $(p,q)$-Elliptic Quasilinear System Under Integral Curvature Condition (Journal of Partial Differential Equations, 2021)
Consider (M,g) as a complete, simply connected Riemannian manifold.The aim of this paper is to provide various geometric estimates in different cases forthe first eigenvalue of $(p,q)$-elliptic quasilinear system in both Dirichlet and Neumannconditions on Riemannian manifold. In some cases we add integral curvature condition and maybe we prove some theorems under other conditions.